Effect of Self-Measuring Blood Pressure Program on Hypertension Control: Analysis by Diabetes Status, Age, Gender, and Race in Rural Arizona - Joy Luzingu; Aminata Kilungo; Randall Flores; Zoe Baccam; Tenneh Turner-Warren; Thelma Reis; Babasola Okusanya; John Ehiri (Clinics and Practice)
Background: Rural areas face numerous health challenges, including workforce shortages, limited training opportunities, and delayed care. These disparities can be mitigated by self-management interventions for diseases such as hypertension. This study assessed the implementation of a Self-Measuring Blood Pressure (SMBP) program in rural Arizona, documenting its barriers and patient experiences. Methods: In this before-after study, participants were loaned a digital device which they used to self-measure and record blood pressure (BP) over 1 week or more for hypertension diagnosis or 4 weeks or more for monitoring. Blood pressure (BP) control was assessed per the guidelines of the American Heart Association and American Diabetes Association. BP changes between baseline and post-program were assessed using paired-Student t tests. Effect modification by diabetes was analyzed using stratification. Results: Among 740 participants, significant associations were found with gender, age, and controlled BP among non-diabetic patients. Post-intervention, 63.4% of diabetic patients showed controlled BP, and 25.7% of non-diabetic patients had controlled BP, with higher control rates among females and older age groups (60–79 years). Baseline mean SBP was 148.3 ± 19.6 mmHg, improving to 133.9 ± 14.6 mmHg; baseline DBP was 88.5 ± 33.6 mmHg, improving to 83.4 ± 9.6 mmHg. Conclusions: The SMBP program effectively controlled BP, highlighting the value of combining clinical care with telemonitoring.